Analysis of the Implementation of the Merdeka Curriculum in Supporting Student-Centered Learning in Elementary Schools - Nensi Desiana Purnamasari; Kayla Hajar Zahira; Bambang Sumardjoko; Sabar Narimo (Lembaran Ilmu Kependidikan, 2026)
Background - The Merdeka Curriculum was introduced as an educational transformation initiative that emphasizes student-centered learning. Purpose - This study aims to analyze the implementation, challenges, strategies, and evaluation of the effectiveness of the Merdeka Curriculum in supporting student-centered learning in elementary schools. Method/approach - This study employs a descriptive qualitative approach, utilizing purposive sampling through data collection via observation and interviews. Findings - The findings indicate that the implementation of the Merdeka Curriculum generally aligns with student-centered learning, characterized by the application of differentiation in content, process, and product. However, challenges remain in its implementation, such as disparities in student participation and varying levels of teacher readiness in adapting learning approaches. Overall, the curriculum’s implementation is proceeding well and demonstrates positive progress in creating a flexible and responsive learning environment. Conclusions - This study emphasize the importance of strengthening teachers’ competencies and adopting inclusive learning strategies to maximize the effectiveness of the Merdeka Curriculum’s implementation. Novelty/Originality/Value - An empirical analysis of the implementation of the Merdeka Curriculum in facilitating student-centered learning in elementary schools, a topic that has yet to be thoroughly explored in the context of Indonesian education.